Improving the accuracy of pancreatobiliary tract cytology with fluorescence in situ hybridization. Issue 11 (30th April 2013) - Kipp, Benjamin R.; Barr Fritcher, Emily G.; Pettengill, Jennifer E.; Halling, Kevin C.; Clayton, Amy C.
<x xml:space="preserve">Abstract</x> The detection of aneuploidy by fluorescence in situ hybridization (FISH) has revolutionized how laboratories diagnose cholangiocarcinoma and pancreatic adenocarcinoma using cytology specimens. Numerous clinical studies have demonstrated that FISH increases the diagnostic sensitivity of routine cytology for detecting pancreatobiliary tract malignancy with minimal decreases in clinical specificity. FISH also provides useful information in difficult clinical scenarios, including the assessment of patients with biliary strictures who have equivocal cytology results and the assessment of patients with primary sclerosing cholangitis who have clinical features suggestive of malignancy. The improved ability to detect pancreatobiliary tract cancers offers the possibility of earlier detection when patients are amenable to surgical intervention and can decrease health care costs by reducing the amount of clinical evaluation required to arrive at a cancer diagnosis. Cytopathology personnel should maintain familiarity with molecular cytology testing methodologies, because morphologic and aneuploidy assessment of tumors will continue to be an integral part of large‐scale genome analyses of individual tumors. Cancer (Cancer Cytopathol) 2013;121:610‐9. © 2013 American Cancer Society.